Yemen : Towards Deeper Trade Integration - World Bank (Washington, DC, 2014)
This note sketches a possible strategy for Yemen to deepen integration with the Gulf Cooperation Council (GCC). It advocates that Yemen put priority on such integration as a complement to its ongoing effort to accede to the WTO, and pause temporarily the implementation of the free trade agreement with Arab League signatories of the Greater Arab free Trade Agreement. As there is no standard set of GCC accession requirements, closer integration with the GCC will require development of specific action plans for the various policy areas covered by the GCC that identify specific measures to be undertaken by Yemen and GCC partners to realize the potential benefits of cooperation.